Impact of Cover Crop Planting Timing and Fallow Management on Biomass Production and Soil Properties in Dryland Cropping Systems - Priscilla Sedem Akporsoe; Augustine Obour; Zachariah C. Carson; Logan M. Simon; John D. Holman (Kansas Agricultural Experiment Station Research Reports, 2025)
Soil health and ecosystem benefits of cover crops (CCs) in semi-arid dryland cropping systems are dependent on CC biomass productivity. The objectives of this study were to evaluate the effects of CC planting time (spring vs. fall) on CC biomass, and fallow management [no-tillage (NT) vs. occasional tillage (OT)] and CC effects on residue cover, and soil aggregate stability in a winter wheat (Triticum aestivum L.)-sorghum (Sorghum bicolor Moench)-fallow (WSF) rotation. The experiment was conducted at the Kansas State University Hearting Beason (HB) Ranch using a split-plot randomized complete block design with four replications. The main plots were crop phase and sub-plot treatments with triticale (×Triticosecale Wittm.), pea (Pisum sativum L.) and rapeseed (Brassica napus var. napus) mixture planted in the fall, oat (Avena sativa L.), triticale and pea CC mixture planted in the spring, NT fallow, and OT fallow. Results showed that CC biomass productivity was not significantly different between fall and spring-planted CCs. However, there was a trend for greater biomass production with fall-planted CCs. This suggests flexibility in planting time for maximizing CC biomass productivity in the WSF rotation. Fall-planted CCs had the highest residue cover (89%), followed by spring planting (81%), and NT (78%), while OT had the lowest (67%) due to increased soil disturbance. Soil aggregate stability was greatest under fall and spring-planted CCs, while OT reduced aggregate stability compared to CCs or NT fallow. These findings showed NT with CCs either planted in the fall or spring can maintain soil health by increasing residue cover and soil aggregation in semi-arid dryland cropping systems.
Keywords: cover crops; fallow management; aggregate stability